Acute Continuous Vertigo - Kerber, Kevin A. (Seminars in Neurology, 2013)
Acute continuous vertigo presentations are among the most feared presentations in medicine. Although a self-limited disorder is the typical cause, a life-threatening stroke can also occur. Differentiating a self-limited disorder from a life-threatening stroke can be a challenge. Routinely collected information—such as stroke risk factors and findings on the general neurologic examination—is not likely to enable the clinician to discriminate between these causes. A focused oculomotor examination is a necessary component of the assessment, but is underused in routine care. The author describes the challenges to diagnosing stroke in cases of acute continuous vertigo and provides an approach to inform decision making at the bedside. Future research is necessary to validate clinical decision support, assess generalizability, and demonstrate its impact on meaningful outcomes.
Keywords: dizziness; vertigo; stroke; vestibular neuritis; clinical decision making